Oncological treatment in Brazil: a gender and region are associated to starting the therapeutics - Chaves, Isabelle Maria dos Anjos; Oliveira, Vitória Alice Alves de; Araujo, Davi Neri; Lopes, Fernanda Freitas Lemos; Queiroz, Artur Trancoso Lopo de; Silva, Maisa Almeida; Queiroz, Alexandre Souza; Tinoco, Lygia Accioly; Fukutani, Kiyoshi Ferreira (Brazilian Journal of Oncology, 2021)
Introduction: Malignant neoplasms are a major public health problem, being the second leading cause of death in the world. In 2012, the Ministry of Health (BR) instituted Law No. 12,732, which grants cancer patients the right to obtain, from the anatomopathological diagnosis, access to the first treatment in the Brazilian Healthcare System - Sistema Único de Saúde (SUS), within up to sixty days. The change in the patient's prognosis is the aim of this program. Objective: To evaluate the panorama of the time to start cancer therapy in Brazil. Methods: This is a cross-sectional and analytical study on the time for the establishment of the beginning of cancer treatment in Brazil, in the period from 2013 to 2019. The data were extracted from the PANEL-Oncology of the informatics department of Unified Health System. Chi-square and Fisher's exact tests were used to analyze proportions and risk ratios, respectively. Results: The percentage of malignant neoplasms that had the longest delay in starting therapy (>60 days) in the country were prostate (59.6%) and cervix (50.9%). As for sex, the delay was present in 36.9% of men and 33.3% of women (p<0.05). Differences in the rates of cancers with and without delay for the institution of treatment are also evident in the Brazilian macroregions (p<0.05). Assessing the odds ratio for delayed cancer treatment, the male gender is shown to be a risk factor (p<0.05) in all regions, except in the North of the country. The risk for delayed treatment differs depending on the type of cancer. Conclusion: Cancers that have a longer delay in starting therapy are those that have health policies aimed at their screening.
Keywords: Oncology; Therapeutics; Risk factors.